Análisis de ventajas y desventajas de la aplicación de auditorías informáticas al sistema contable de la Utmach. - Quezada Bravo, Diana Carolina (My University, 2020)
This documentation addresses the field of accounting auditing through computer systems, as a derivative of the profession it is necessary to know the application of the regulations, the objectives of an audit, to know which and how to measure the variables that affect the financial statements. Contemporary society is characterized by the constant evolution of technology and science, especially in processes related to the treatment of information, especially in matters of transparency and integrity of monetary states, which reflect the solvency, liquidity and efficiency of the administration. The Technical University of Machala is a public institution responsible for training professionals, effectively managing fiscal resources and researching in the various fields of application for social welfare; but he is also responsible for accountability, consolidating large amounts of data or monetary flows in order to comply with Ecuador's legal specifications. The document has the objective of analyzing the advantages and disadvantages of the computer audit to the accounting system of the Utmach to boost the process through the office automation of the software. An analytical and inductive methodology is applied, building criteria based on a literary review to express the arguments that support the solution of the practical case.
La presente documentación aborda el campo de la auditoría contable mediante sistemas informáticos, como derivado de la profesión es necesario conocer la aplicación de las normativas, los objetivos de una auditoria, saber cuáles y cómo medir las variables que inciden en los estados contables. La sociedad contemporánea se caracteriza por la evolución constante de la tecnología y ciencia, en especial en procesos afines al tratamiento de informaciòn, más aún en cuestiones de transparencia e integridad de estados monetarios, que reflejan la solvencia, liquidez y eficiencia de la administración. La Universidad Técnica de Machala es una institución pública encargada de formar profesionales, gestionar eficazmente los recursos fiscales e investigar en los diversos campos de aplicación para bienestar social; pero también es responsable de rendir cuentas, afianzar grandes cantidades de datos o flujos monetarios a fin de cumplir con las especificaciones legales del Ecuador. El escrito tiene el objetivo de analizar las ventajas y desventajas de la auditoria informática al sistema contable de la Utmach para dinamizar el proceso a través de las prestaciones ofimáticas del software. Se aplica una metodología analítica e inductiva, construyendo criterios en base a una revisión literaria para expresar los argumentos que sustenten la solución del caso práctico.
Keywords: AUDITORIA INFORMÁTICA; SISTEMAS CONTABLES; VENTAJAS; DESVENTAJAS; INSTITUCIONES DE EDUCACIÓN SUPERIOR (IES)